Academic procrastination, self-esteem, and self-efficacy in first-term university students in the city of Lima - Arias-Chávez, D. (2020)
The purpose of this study is to determine the relationship between academic procrastination and self-esteem and self-efficacy in university students in metropolitan Lima, 2019. The population consisted of 5,800 students, from which a sample of 566 subjects was extracted (283 male, 283 female), aged between 16 and 19 years. The study subjects were selected from the first two terms of 5 universities (4 private and 1 public) in metropolitan Lima. The following instruments were used: The Academic Procrastination Scale (APS), the Specific Perceived Self-efficacy Scale of Academic Situations (SPSSAS) and the Rosenberg Self-Esteem Scale, the same that evidenced having psychometric properties of reliability (the method of applying internal consistency) and construct validity (an exploratory factor analysis was performed). The results show that there is a relationship between self-esteem and academic procrastination as Spearman’s correlation is -.163, the effect size is 0.4037 and the statistical power is 1.00. While the ratio between procrastination and self-efficacy is -.220, the size of the effect is 0.4690, and the statistical power exceeds 0.80, obtaining the value of 1.00. It is concluded that in both cases there are very weak type correlations. However, the effect size is large and the statistical power is very high.